Analysis of effective environmental factors an urban health, a case study of Qom, Iran. (July 2016) - Mahdi, Ali; Hosseini, Ali; Pourahmad, Ahmad; Hataminejad, Hossein
Abstract: As the habitat of the urban man, city is need of meeting standards which can be called standards of health and quality. In fact, life health is a multi-dimensional and complicated concept which is emphasized by social and urban scholars. A ware of the importance of this issue, the present research studies the issue of urban health from the perspective of environmental studies. This research, which is an applied research whose research method is also based on case study, has made use of descriptive – analytic method to study the two variables. On this basis, 384 questionnaires were distributed among household heads (level of analysis) in eight districts of Qom (the area case study). Finally, in order to analyze the resulting data, questions which were posed, were explained through using SPSS and TOPSIS method along with the related models. The study shown that the eight district of case study, under the influence of social, economic, and cultural circumstances as well as the quality of interaction with urban management, have a kind of spatial division regarding environmental quality and urban health in a way. Districts 1, 4, 3 and 7 benefit from a better landscape and environmental quality, regarding the above-mentioned circumstances, in comparison to districts 2 6, 5 and 8. Overall, regarding the present status of environmental quality, we presently witness the existence of an access or lack of access to urban health factors in Qom.